PENGEMBANGAN E-LKPD INTERAKTIF BERORIENTASI SETS DENGAN LIVEWORKSHEET UNTUK MENINGKATKAN MINAT DAN HASIL BELAJAR SISWA - Dede Daud (Media Bina Ilmiah, 2024)
Achievements of low interest and learning outcomes in Biology, especially in the Human Immune System subject at SMA Negeri 10 Pekanbaru prompted the development and measurement of the validity, practicality, and effectiveness of the interactive E-LKPD oriented towards SETS with liveworksheet to enhance student interest and learning outcomes. The development method used is the ASSURE method, employing data collection techniques through interviews, questionnaires, and learning outcome tests. Data analysis involves calculating respondent answer scores, t-tests, and n-gain tests. The average scores, based on validity criteria, assessed in terms of material, media usage, and pedagogical aspects, fall within the interval of average scores >3.25 – 4, categorizing it as Very Valid. The practicality of E-LKPD, assessed by both teachers and students, falls within the interval of average scores >3.25 - 4, categorizing it as Very Practical. There is an increase in student interest from 68% before use to 82% after using E-LKPD. The t-test and n-gain score results indicate a significant difference in the improvement of learning scores between the experimental and control groups, indicating that the developed E-LKPD is effective in improving student learning outcomes.